How do exhausted parents experience their interactions with their children? A qualitative and participative study - Dubois, Anne-Catherine; Roberti-Lintermans, Margaux; Mallien, Zoé; François, Aurore; Lahaye, Magali; De Mol, Jan; Aujoulat, Isabelle (Frontiers in Public Health, 2024)
Introduction Parental burnout, known as a state of physical and psychological exhaustion, results in an imbalance between the parent’s perceived stressors in relation to parenting, and the resources available to the parent to cope with such stressors. The causes and consequences of parental burnout for the parents themselves have been studied from the parents’ point of view, but the perception of parents regarding the impact of parental burnout on the parent-child relationship has not yet been documented. Methods We conducted a qualitative study through semi-structured interviews with exhausted parents (n=21). We aimed to better understand their general interactions with their children, as well as the way they communicate with them about their state of exhaustion, knowing that dealing with parental suffering can have a long-term impact on the child. Results Our results reveal that exhausted parents experience a widespread loss of control in all areas of their lives, particularly in their interaction with their children, which generates feelings of guilt and shame. Communicating their experience to their children can create various difficulties for both parents and children. This may complicate the process of seeking help and reinforce the feeling of isolation. Discussion An emerging result from our analysis leads us to identify a need for the parents to be heard and validated in their suffering who took part in this research.